Etiology of blood culture isolates among patients in a multidisciplinary teaching hospital in Kuala Lumpur - Karunakaran, R.; Raja, N.S.; Ng, K.P.; Navaratnam, P. (2007)
Bloodstream infections are an important cause of morbidity and mortality among hospitalized patients and the surveillance of etiological agents in these infections is important for their prevention and treatment. Data on common organisms isolated from blood cultures from Malaysia are limited, and our aim was to identify the common bloodstream isolates in hospitalized patients at the University of Malaya Medical Centre (UMMC), Kuala Lumpur, Malaysia. A retrospective analysis was conducted over a 1-year period from January to December 2004 by reviewing laboratory reports of patients from the UMMC. The clinical significance of the isolates was not analyzed. Coagulase-negative staphylococci were the most common organisms isolated, accounting for 33.0% of the total blood culture isolates, followed by Staphylococcus aureus (10.4%) and Escherichia coli (9.7%). The incidence of methicillin-resistant S. aureus, and extended-spectrum beta-lactamase-producing E. coli and Klebsiella spp. bacteremia was low (2.3% and 1.8% of total isolates, respectively). Non-albicans Candida were the most common fungal isolates. Conclusions: The high number of coagulase-negative staphylococci should motivate clinicians and microbiologists to re-examine blood culture techniques in our institution. We recommend that further studies be carried out to establish the true significance of this organism among blood culture isolates.